2015
DOI: 10.1016/j.proeng.2015.12.543
|View full text |Cite
|
Sign up to set email alerts
|

An Industrial System for Estimation of Workpiece Height in WEDM

Abstract: The wire electrical-discharge machining process (WEDM) is a widely-used technology which can achieve the requirements needed by industry, such complex geometries and precision. Cutting process control in WEDM becomes essential in terms of surface finish and dimensional tolerances. When a cut is made in a variable workpiece thickness, the process becomes very unstable in the transition zone. The difference of energy related to the WEDM regime cannot be easily accommodated when changing to another thickness. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Still, there are some disputes involved in WEDM such as the selection of various AE materials, selection of suitable advanced wire materials, and micro-machining of hard ceramics, these issues should be examined and discussed in further research works, 29,43 and. 48 A process map to select a suitable AE including various methods to apply AE on the base material and its results may help in evolving significant understandings regarding the machining of these ceramics.…”
Section: Future Visions Of This Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, there are some disputes involved in WEDM such as the selection of various AE materials, selection of suitable advanced wire materials, and micro-machining of hard ceramics, these issues should be examined and discussed in further research works, 29,43 and. 48 A process map to select a suitable AE including various methods to apply AE on the base material and its results may help in evolving significant understandings regarding the machining of these ceramics.…”
Section: Future Visions Of This Researchmentioning
confidence: 99%
“…The addition of zinc to the copper electrode also helps to governor discharge properties, which made the brass electrode the most efficient alternative for general-purpose EDM and WEDM. Now a day we can find an extensive variety of tensile strength and hardness by varying the alloying percentage of zinc, 24,27,42,43 and. 44 Moreover, a comparative study of the influence of conventional copper wire and brass wire have been performed during machining of EN 8 steel.…”
Section: Brass Wiresmentioning
confidence: 99%
“…16 Such temperature melts and vaporizes a very tiny amount of workpiece material, so the WEDM can achieve very low surface roughness (less than 0.2 mm of average roughness, Ra). 17 The wire is held between the upper and lower diamond guides with a specific tension, unwound from a spool, fed through the workpiece, and then wound to another spool. The performance of WEDM is usually measured by the cutting speed, surface roughness, and dimension accuracy of the workpiece.…”
Section: Development Of a Cps Based On The 8c Architecturementioning
confidence: 99%
“…On the one hand, the data-information conversion can be realized at the RFID reader, BT reader, PLC, or gateway as long as enough computing resources are available in it. This is actually the concept of fog computing, which is defined in Conde et al 17 as ''an architecture that uses one or more collaborative multitude of end-user clients or near-user edge devices to carry out a substantial amount of storage, communication, control, configuration, measurement and management.'' On the other hand, the conversion can be carried out at the cloud side which is abundant in computing resources.…”
Section: Focus On Both Vertical Integration and Horizontal Integrationmentioning
confidence: 99%
“…Based on the experiments, an effective method has been suggested to eliminate the inaccuracy of the profile, which will lead to a better understanding of the gap force phenomenon. Conde et al 8 studied the most important variables used in the WEDM process. The results presented in the experiment showed that the workpiece thickness determination can be achieved by the analysis of the variable Gap error, which is built as a combination of Ionization time and servo voltage.…”
Section: Introductionmentioning
confidence: 99%